Analisis Pengaruh Rasio Likuiditas, Solvabilitas dan Profitabilitas terhadap Return Saham - Maria Yanita Sanjaya; Alfiatul Maulida (MES Management Journal, 2023)
This study aims to determine the effect of liquidity ratios, solvency and profitability on stock returns. This study used the population of food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sampling is carried out by purposive sampling method. The data analysis method used in this study is multiple linear regression analysis. The results of this study found that liquidity measured using the current ratio negatively affects stock returns. Meanwhile, solvency (Debt to Equity Ratio) and profitability (Return on Assets) have a positive effect on stock returns. Keywords: Liquidity, solvency, profitability, stock returns